Problems Facing Undergraduate Students At Al Ghad International College For Health Sciences: Basis To Improve Academic Performance - Paul Reinald Base Garcia; Yasser Adnan Abu Jaish (European Scientific Journal, ESJ, 2016)
This action research has sought answers to the following research questions: What are the problems encountered by the low performing students of different departments in terms of psychosocial, psychological and educational? What are the proposed specific measures geared towards the enhancement of learners’ academic performance? Researchers have utilized a mixed method research design, both quantitative and qualitative methods which gave them greater confidence in establishing conclusion of the study. They have figured out specific measures to address problems in terms of psychosocial, psychological and education domains confronting the subjects of the study. These proposed measures are adaptation of academic performance flow chart and the revised attendance grading scheme. The authors also suggest the preparatory department to create an English proficiency committee which will design English proficiency programs for this low performing group zeroing in listening, reading, writing and speaking proficiencies. They also propose for the College to use better software management system and to conduct an annual departmental curriculum review and enhancement. They have included all of the students with GPA 2.75 and less from different departments of Al-Ghad International College Dammam Male Campus, a large and young private academic institution which offers various health care programs as participants of the study. A self-made questionnaire has been constructed and has become the main tool to gather the necessary data and interview has done to dissect the variables under scrutiny. Researchers have also used a standardized test (Kessler Psychological Distress Scale) which determined the psychological distress status of the subject learners. The gathered numeric data have been tabulated, evaluated, analyzed and interpreted using Statistical Package for Social Science (SPSS) version 22.